Cover Image. (24th June 2022) - Pérez‐Rosales, Gonzalo; Pichon, Michel; Rouzé, Héloïse; Villéger, Sébastien; Torda, Gergely; Bongaerts, Pim; Carlot, Jérémy; ,; Parravicini, Valeriano; Hédouin, Laetitia
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13549 "Mesophotic coral ecosystems of French Polynesia are hotspots of alpha and beta generic diversity for scleractinian assemblages" by Gonzalo Pérez‐Rosales et al. A quantitative study in French Polynesia suggests mesophotic coral ecosystems are biodiversity hotspots and recommends their consideration in the conservation planning of coral reefs. Photo Credit: Julien Leblond/Under The Pole/Zeppelin Network.